Effect of the hatching month as an environmental factor on the hatching features of bronze turkeys - Ozcelik, Mahiye; Cerit, Harun; Ekmen, Fikriye; Dogan, Ismet (Tubitak Scientific & Technological Research Council Turkey, 2006)
The aim of this study was to determine the effect of hatching month on the hatching features of Bronze turkeys, and to determine the suitable months for hatching. For this purpose, the hatching records of Bronze turkeys raised in the Bingol Beekeeping and Turkey Production Station from 1998 to 2003 were used. Egg fertility and hatchability of both total eggs and of fertile eggs were investigated, and it was found that the effect of hatching month on all 3 variables was statistically significant. The results regarding all 3 variables were lower in June as compared to the other months investigated. For this reason, it was concluded that hatching should not be performed in June, when temperatures increase sharply.
Keywords: turkey; hatching month; hatching season; egg fertility; hatchability